Global Ripple Effects of the Trump Tariff War on Trade, Economic Growth, and Inflation - Behera, Janardan (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
The United States’ imposition of tariffs during the Trump presidency between 2018 and 2020 activated one of the largest trade disputes in recent economic history. This analysis studies the international ripple effects of the tariff actions on international trade flows, economic growth, and inflation across both emerging and developed economies. Utilizing a balanced panel dataset of 70 nations between 2015 and 2022, the analysis uses fixed effects as well as dynamic panel regression specifications to approximate the short- as well as medium-term trade contraction shocks that tariffs cause. The study demonstrates that increased tariff exposure significantly reduced world trade volumes, as well as considerably decreased GDP growth rates, yet at the same time, it caused weak yet persistent inflationary pressures through disintegrated supply chains and increased import costs. The study demonstrates the asymmetry of the effect, with developing nations experiencing higher exposure to trade contraction. The study demonstrates the wider macroeconomic costs of protectionist trade policies as well as the importance of revived multilateral cooperation to stabilize markets globally as well as achieve sustainable growth.